OBSTETRIC OUTCOMES IN WOMEN WITH RH IMMUNIZATION (World Bulletin of Public Health, 2024)
Among the current problems of practical obstetrics, one of the most important places is occupied by the problem of immunoconflict pregnancy. Starting from the first weeks of pregnancy, complex immunobiological relationships arise between the embryo and the maternal body, which largely determine the further course of pregnancy, the condition of the mother, and the development of the fetus and newborn. The cause of the development of hemolytic disease of the fetus and newborn is immunization of the maternal body with fetal red blood cells containing antigens that are absent in the mother. Most often this refers to the Rh system (95%), less often to the AB0 system and other antigenic factors of erythrocytes. The Rh factor begins to form at 7-8 weeks of pregnancy and is clearly visible in the fetus at 10-14 weeks. A necessary condition for the development of hemolytic disease of the fetus and newborn is the passage of fetal red blood cells through the placental barrier into the mother's bloodstream. In this case, the first entry of fetal erythrocytes containing Rh0 (D) into the mother’s bloodstream leads to her sensitization, that is, to the production of antibodies, and the second one may be accompanied by a Rh conflict, that is, an antigen-antibody reaction, which is the basis for the development of HDN
Keywords: Hemolytic disease of the fetus; hemolytic disease of the newborn; Rh immunization